Assessment of aluminium level in commercial pasteurized and UHT milk in Bangladesh and their potential health risks - Ishrat Jahan; Kazi Md. Al-Noman; Shabbir Ahmed; Mst. Umme Habiba; S. A. Masudul Hoque; Abu Sadeque Md. Selim; Md. Morshedur Rahman (Journal of Advanced Biotechnology and Experimental Therapeutics)
Aluminium (Al) contamination in the dairy industry is an emerging concern due to potential health risks. With the increasing consumption of pasteurized and UHT milk in Bangladesh, monitoring Al levels has become crucial. This study aimed to measure Al concentrations in these processed products using inductively coupled plasma mass spectrometry (ICP-MS) and assess the associated health risks. Milk samples from 10 brands, including three different production lots, were collected from supermarkets. The instrumental precision for Al was 0.0212 mg/kg as a limit of detection (LOD) and 0.0643 mg/kg as a limit of quantification (LOQ), with a relative standard deviation (RSD) of 3.2%. The multi-element standard containing Al exhibited linearity in the concentration ranged from 0-0.5 mg/kg with a correlation coefficient value of 0.9994. Among the 30 samples analyzed, 13, including both pasteurized and UHT milks, were contaminated with Al. The mean Al concentrations in the contaminated samples were 0.46±0.5, 0.71±0.6, and 0.47±0.4 mg/kg in lots 1, 2, and 3, respectively, indicating variation across production lots. The estimated daily Al intake ranged from 2.00E-03 to 3.00E-03 mg/kg body weight, contributing 1.4 to 2.1% of the provisional tolerable weekly intake. The target hazard quotient (THQ) for the contaminated samples ranged from 0.045 to 0.070 (THQ < 1), suggesting that the Al levels pose no significant health risk. Thus, the Al content in pasteurized and UHT milk may be considered safe for consumption, albeit with the limitation of a small sample size in this study. [ J Adv Biotechnol Exp Ther 2025; 8(1.000): 105-115]